2002
DOI: 10.1074/jbc.m111515200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Active Site of Poly(A)-specific Ribonuclease by Site-directed Mutagenesis and Fe2+-mediated Cleavage

Abstract: Poly(A)-specific ribonuclease (PARN) is the only mammalian exoribonuclease characterized thus far with high specificity for degrading the mRNA poly(A) tail. PARN belongs to the RNase D family of nucleases, a family characterized by the presence of four conserved acidic amino acid residues. Here, we show by site-directed mutagenesis that these residues of human PARN, i.e. 2؉ binding at both sites were affected in PARN polypeptides in which the conserved acidic amino acid residues were substituted to alanine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 35 publications
5
54
0
3
Order By: Relevance
“…Some activity could be recovered from the PARN(D382C) mutant after several hours of incubation, although we never managed to detect any hydrolytic activity when using the other cysteine-substituted PARN mutants (data not shown). This suggests that all these conserved acidic amino acid residues are essential for PARN activity, in keeping with our previous results (13).…”
Section: Parn Mutants With Cysteine Substitution In the Active Site Asupporting
confidence: 92%
See 4 more Smart Citations
“…Some activity could be recovered from the PARN(D382C) mutant after several hours of incubation, although we never managed to detect any hydrolytic activity when using the other cysteine-substituted PARN mutants (data not shown). This suggests that all these conserved acidic amino acid residues are essential for PARN activity, in keeping with our previous results (13).…”
Section: Parn Mutants With Cysteine Substitution In the Active Site Asupporting
confidence: 92%
“…However, it remains to be shown that the glutamic acid residue Glu-30 coordinates a divalent metal ion, although available data show that Glu-30 is essential for PARN activity (Fig. 3) and important for the interaction of divalent metal ions (13). Most likely the introduction of a cysteine residue at this position severely affects both the divalent metal ion coordination properties, caused by the replacement of an oxygen atom by sulfur, and the configuration of the PARN active site, because cysteine lacks one methylene group in its side chain compared with glutamate, making it impossible to rescue this particular mutant by replacing Mg 2ϩ with a soft divalent metal ion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations